The effect of grape seed extract on radiation-induced oxidative stress in the rat liver - Aysun ÇETİN; Leylagül KAYNAR; İsmail KOÇYİĞİT; Sibel Kabukçu HACIOĞLU; Recep SARAYMEN; Ahmet ÖZTÜRK; Okan ORHAN; Osman SAĞDIÇ (Turkish Journal of Gastroenterology, 2019)
-